Blue sky thinking meets green field usability: Can mobile internet software engineering bridge the rural divide?. (September 2014) - Morgan, Andrew; Dix, Alan; Phillips, Mike; House, Chris
Mobile applications (apps) are becoming more commonplace as mobile phones and tablets begin to replace traditional desktop devices. Software developers are usually located in areas where good connectivity is the norm, but large numbers of users are located in other areas where 3 G connectivity is at best poor or non-existent. This results in app development which is unsuitable for many areas of the world and, as well as being a problem in rural areas of the UK, has ramifications for mobile app use in third world countries where fixed broadband services are largely absent. Drawing on experiences of users on the margins of connectivity, this paper discusses difficulties of mobile internet access in Wales and recommends changes to app development methodology to maximise bandwidth in areas of limited network coverage.